2015 revised Utstein-style recommended guidelines for uniform reporting of data from drowning-related resuscitation: An ILCOR advisory statement. (September 2017) - Idris, Ahamed H.; Bierens, Joost J.L.M.; Perkins, Gavin D.; Wenzel, Volker; Nadkarni, Vinay; Morley, Peter; Warner, David S.; Topjian, Alexis; Venema, Allart M.; Branche, Christine M.; Szpilman, David; Morizot-Leite, Luiz; et al.
Abstract: Background: Utstein-style guidelines use an established consensus process, endorsed by the international resuscitation community, to facilitate and structure resuscitation research and publication. The first "Guidelines for Uniform Reporting of Data From Drowning" were published over a decade ago. During the intervening years, resuscitation science has advanced considerably, thus making revision of the guidelines timely. In particular, measurement of cardiopulmonary resuscitation elements and neurological outcomes reporting have advanced substantially. The purpose of this report is to provide updated guidelines for reporting data from studies of resuscitation from drowning. Methods: An international group with scientific expertise in the fields of drowning research, resuscitation research, emergency medical services, public health, and development of guidelines met in Potsdam, Germany, to determine the data that should be reported in scientific articles on the subject of resuscitation from drowning. At the Utstein-style meeting, participants discussed data elements in detail, defined the data, determined data priority, and decided how data should be reported, including scoring methods and category details. Results: The template for reporting data from drowning research was revised extensively, with new emphasis on measurement of quality of resuscitation, neurological outcomes, and deletion of data that have proved to be less relevant or difficult to capture. Conclusions: The report describes the consensus process, rationale for selecting data elements to be reported, definitions and priority of data, and scoring methods. These guidelines are intended to improve the clarity of scientific communication and the comparability of scientific investigations.